Kepribadian Machiavellianism pada Aspek Perilaku Auditor - Sagara, Yusar; Atikah, Nur (Jurnal Kajian Akuntansi, 2021)
AbstractThe historical development of audit practices is inseparable from various cases of ethical violations and deviations from audit standards. This behavior is explained as a dysfunction behavior that is closely related to today's modern human profession. This study discusses how machiavellian tendencies in a person are very closely related to behavioral dysfunction in the auditor and how spiritual concepts in the workplace become a solution in preventing and minimizing these attitudes and behaviors. The study was conducted on 115 auditors in the Jakarta public accounting firm through a survey. The data analysis method used is quantitative data analysis with Structural Equation Modeling (SEM) approach assisted by the LISREL 8.80 program. Data processing results show that workplace spirituality has a significant negative effect on audit dysfunction behavior through machiavellian nature, but does not have a negative and significant effect directly on dysfunction behavior.Keywords: Attribution theory; Audit dysfunction behavior; Machiavellian tendencies; Workplace spirituality. Abstrak Sejarah perkembangan praktik audit tidak terlepas dari berbagai kasus pelanggaran etika dan penyimpangan atas standar audit. Perilaku tersebut dijelaskan sebagai perilaku disfungsi yang erat kaitannya dengan profesi manusia modern saat ini. Penelitian ini membahas bagaimana kecenderungan machiavellian dalam diri seseorang sangat erat kaitannya dengan perilaku disfungsi dalam diri auditor dan bagaimana konsep spiritual di tempat kerja menjadi solusi dalam mencegah dan meminimalisir sikap dan perilaku tersebut timbul. Penelitian dilakukan kepada 115 auditor di kantor akuntan publik DKI Jakarta melalui survei. Metode analisis data yang digunakan yakni analisis data kuantitatif dengan pendekatan Structural Equation Modeling (SEM) berbantuan program LISREL 8.80. Hasil pengolahan data menunjukkan bahwa workplace spirituality berpengaruh negatif secara signifikan terhadap perilaku disfungsi audit melalui sifat machiavellian, tetapi tidak berpengaruh negatif dan signifikan secara langsung terhadap perilaku disfungsi.Kata kunci: Teori atribusi; Perilaku disfungsi audit; Sifat machiavellian; Workplace spirituality.